The interfacial charge transfer in triphenylphosphine-based COF/PCN heterojunctions and its promotional effects on photocatalytic hydrogen evolution. (17th May 2021) - Tang, Jie; Li, Qi; Liu, Yubing; Xu, Naizhang; Wang, Kaiqiang; Zhang, Qitao; Yang, Wenjuan; Fan, Yining
Abstract: In this study, the novel triphenylphosphine-based covalent organic frameworks (P–COF-1) were firstly introduced into polymeric carbon nitride (PCN) to fabricate P–COF-1/PCN heterojunctions via intermolecular π-π interaction. The photocatalytic H2 production rate over the 9% P–COF-1/PCN heterojunctions is ca. 12 times as much as that of pure PCN. The photoelectrochemical measurements and theoretical calculation results show that due to the well-matched band structure between P–COF-1 and PCN, the photo-generated electrons tend to migrate from P–COF-1 into the conduction band of PCN through the interface of heterostructures. In addition to the π→π∗ electron transition of conjugated tri- s -triazine units in the 9% P–COF-1/PCN with band gap energy of 2.53 eV, the lone pair electrons of P transition to the π∗ orbitals of P–COF-1 (n→π∗) with lower band gap energy of 1.82 eV results in the effective separation of photo-generated carriers and more visible light absorption, and thus enhanced the photocatalytic hydrogen evolution. Highlights: The P–COF-1/PCN heterojunctions were firstly fabricated by π-π interaction. The n.→π∗ electron transition was induced in the P–COF-1/PCN heterojunctions. Hydrogen production rate was enhanced over the 9% P–COF-1/PCN heterojunctions.